2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090236
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interval training compared with endurance training in cardiac rehabilitation

Abstract: Anaerobic endurance training (AET) can improve sympathomimetic hyperactivity, and anaerobic interval training (AIT) is recommended for patients who cannot exercise due to exertional breathlessness and leg fatigue. However, the difference in sympathetic nerve activation (SNA) and parasympathetic nerve activation (PNA) during AIT and AET is unclear. The aim of this study is to investigate the differences between endurance and interval trainings. We studied three patients (63-73 years) assigned to AIT which exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This corresponds well with the finding from García-Hermoso et al who observed similar results albeit in overweight and obese youth (Garcia-Hermoso et al, 2016 ). It is speculated that this might be partly explained by the evidence that INT could result in a higher reduction of sympathetic nervous activity (Hanada et al, 2011 ; Ciolac, 2012 ) as well as a larger improvement in endothelial function than MICT (Ciolac, 2012 ; Mitranun et al, 2014 ; Ramos et al, 2015 ), both factors are closely related to SBP control (Wallace et al, 2007 ; Flaa et al, 2008 ). Moreover, the INT-induced increases in shear stress might be another mechanical possibility (Adams et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds well with the finding from García-Hermoso et al who observed similar results albeit in overweight and obese youth (Garcia-Hermoso et al, 2016 ). It is speculated that this might be partly explained by the evidence that INT could result in a higher reduction of sympathetic nervous activity (Hanada et al, 2011 ; Ciolac, 2012 ) as well as a larger improvement in endothelial function than MICT (Ciolac, 2012 ; Mitranun et al, 2014 ; Ramos et al, 2015 ), both factors are closely related to SBP control (Wallace et al, 2007 ; Flaa et al, 2008 ). Moreover, the INT-induced increases in shear stress might be another mechanical possibility (Adams et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%